Converging Flow Passages, Nanofluids and Magnetic Field: Effects on the Thermal Response of Microchannel Heat Sinks - Amir Fattahi; Maziar Dehghan; Mohammad Sadegh Valipour (Journal of Heat and Mass Transfer Research, 2022)
To analyze the possibility of heat transfer enhancement of micro-scale heat exchangers, the transport phenomena of water (H2O) - Aluminum oxide (Al2O3) nanofluid in a three-dimensional microchannel with converging flow passages in the presence of a magnetic field are numerically investigated. All simulations are performed for the Harman number (Ha) of 0-20 and the volume fraction of ∅ = 0 and 0.02 in the laminar regime (Reynolds number, Re, < 100). The magnetic field is applied in the normal direction (with respect to the flow direction). The results show that the convection heat transfer coefficient, as well as the friction factor, increases with the increase of the Hartman number. The increase in the friction factor is noticeable up to being doubled while the increase of the convection heat transfer coefficient is up to 20 %. The uniform velocity arising from the magnetic field presence gives almost uniform temperature distributions in the fluid and solid parts of the micro-channel, which makes removing higher heat fluxes within the safe temperature limit possible. Although the heat transfer performance enhances with the increase of the magnetic field, the rate of heat transfer enhancement decreases with the increasing magnetic field. In other words, the magnetic field has a maximum effective value and there is no justification for a further increase according to the energy efficiency perspectives. It should be noted that the mentioned limits for magnetic field (here, presented with Ha) are very high and almost impossible to be applied at micro-scales. In addition, the effect of the magnetic field on the velocity profile decreases with the increase of the passage convergence. In other words, the flow convergence eliminates the need for a high magnetic field to have a uniform velocity profile and as well a uniform temperature distribution.